Reservoir Characteristics and Controlling Factors of Oil Content in Hybrid Sedimentary Rocks of the Lucaogou Formation, Western Jimusar Sag, Junggar Basin - Xue, Haitao; An, Ce; Dong, Zhentao; Xiao, Dianshi; Yan, Jinliang; Ding, Guozhi; Yan, Penglei; Zhang, Jinxu (Frontiers in Earth Science, 2021)
Hybrid sedimentary rocks (HSR) are a major reservoir type in unconventional oil exploration. The reservoir characteristics and controlling factors of the oil content of HSR are not clear, restricting the understanding of the storage mechanism and sweet spots within HSR. The Lucaogou Formation in the western Jimusar Sag is taken as a case study. Starting with the classification of the lithofacies system, differences in the microscopic pore structure, oil content and controlling factors of HSR reservoirs are revealed. The results show that seven lithofacies are recognized based on mineral composition, sedimentary structure, and organic matter characteristics, exhibiting rapid vertical and horizontal changes affected by the sedimentary environment. Layered mudstone lithofacies of the shallow lake mud and massive dolomitic mudstone lithofacies of dolomitic mud flats have the worst physical properties and oil content properties. However, they do have high organic matter contents and are the main source rocks of the Lucaogou Formation. The massive argillaceous siltstone and massive argillaceous dolomite lithofacies interbed frequently. Although their physical properties are moderate, “source-reservoir integrated” unconventional oil reservoirs can be formed, due to the adjacent to the source rock. Massive dolomitic siltstone, massive siltstone, and massive silty dolomite lithofacies are developed in the middle of the Lucaogou Formation, with the highest proportion of mesopores and macropores, which is indicative of good storage properties. When these lithofacies are filled with crude oil generated from source rocks at the top and bottom of the formation, “source storage adjacent” unconventional oil reservoirs be formed. The oil content is also controlled by the pore structure and specific surface area. The proportion of macropores and mesopores is positively correlated with oil content. The oil content of the samples is very low, when the specific surface area exceeds 2 m2/g. This manuscript provides a geological basis for evaluating and establishing reasonable interpretation models of HSR sweet spots.